P4.114 Sexual Behavior and Practice Among Transgenders in West Bengal, India. (13th July 2013) - Kundu, M; Panda, N; Chowdhury, S; konar, S Das; Basu, R; Das, D; Sonkar, R; RoyChoudhury, A
Abstract : HIV Epidemic in India is not generalised but is a concentrated epidemic. The Prevalence of HIV among Transgender is 8.82, thus there is the necessity for specific programmes. Hence, a study among the transgender conducted to know the sexual behaviour & practise among them. A structured questionnaire had been developed followed by training of the interviewer. The respond Driven Sampling method was used. The study had been conducted in collaboration with Community Based Organization working with Transgender in West Bengal. According to this study the 30% & 42% respondents have secondary and graduate level of education whereas 28% are post graduate. 25% populations below 18 years have more than 10 sexual partner and 18 years above have 7 partners on an average in a month. 43% respondents have exposure of sexual intercourse before the age of 13 & rests 57% between the ages 14 to 18. 12% are married with female but all of them preferred & practise anal sex and have multiple male sexual partners. 81% contact with their partners through mobile phone or use e-communication which hampers the so called Outreach concept. 88% do not know about the sign & symptoms of STI but 67% of them being affected with it. 83% are inconsistent condom user and they have complained of condom rupture during sex & unavailability of lubricant. 80% populations have self risk perception to get HIV. Indian National HIV Programme Design need to cater specific need based tailor made Transgender Programme. Need convergence of Adolescent & HIV Programme for Transgender. Incorporate Social Media, phone in new outreach strategy for more reaching out. National HIV prevention Programme needs specific male STI Guideline. The Self Risk perception among this community is very high so immediate new programme strategy will help the Transgender Community to prevent HIV.